THE EFFECT OF MINGLE GAME ON STUDENTS’ SPEAKING DESCRIPTIVE TEXT ABILITY (A Study at the Seventh Grade Students of SMP Swasta Sariputra in 2018/2019 Academic Year - Nurlisa Novitasari Parinduri (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: The purposes of this research are to find out: 1) The application of Mingle Game in teaching speaking descriptive text, 2) Students’ speaking descriptive text ability before and after using Mingle Game, 3) whethere there is a significant effect of using Mingle Game at the seventh grade students of SMP Swasta Sariputra. Method of this research is experimental method. The population of this research are all of the seventh grade students of SMP Swasta Sariputra that consists of 62 students. Systematic sampling technique is used to get the sample of research, the sample consist of 31 students. The technique for collecting data are observation sheet and test. The result of the application of mingle game is 3.6, it is categorized “Very Good”. Before using mingle game is 38.29, it is categorized “Fail”. Meanwhile, after using mingle game is 63.75, it is categorized “Enough”. The result of ttest is 12.02 and t table is 2.04, it means that there is a significant effect of using mingle game on students’ speaking descriptive text ability at the seventh grade students of SMP Swasta Sariputra in 2018/2019 Academic Year.